The Effect of Extract of Getih-Getihan (Rivina humilis L.) on Armyworm (Spodoptera litura F.) Mortality - Dewi Nurhayati; Wachju Subchan; Jekti Prihatin (BIOEDUKASI, 2018)
Armyworm (Spodoptera litura F.) is a leaf-eating pest causes the loss of crops from 85% until causing crop failure. Alternative pest control and to reduce the negative impact of synthetic pesticides include using botanical pesticide. Getih-getihan plant (Rivina humilis L.) is one of the plants having potency as a botanical pesticide. Based on the description, this study was conducted to determine LC50 value by using probit analysis and analysis of an extract of Rivina humilis L. leaves on the mortality of Spodoptera litura F. using ANOVA test. Rivina humilis L. leaves are extracted by using ethanol solvent to get active chemical to kill Spodoptera litura F.. TLC (Thin Layer Chromatography) result test of an extract of Rivina humilis L. are positively contain an alkaloid, flavonoid, tannin, and terpenoid. The method of the research uses CRD (Complete Random Design) with five times repetition. Concentration serial being tested are 0%, 0.5%, 1%, 1.5%, 2%, and 2.5%. The result of probit analysis is 1.42% of LC50 value and ANOVA test shows that extract of Rivina humilis L. leaves affects very significantly on the Spodoptera litura F. mortality (p=0.000). Keywords: Spodoptera litura F., Rivina humilis L., leaves extract.